Relative Risk (RR) Analysis and Prediction as Part of Assessing Occupational Safety and Determining Priorities for Action in Occupational Health and Safety in the Construction Industry in Poland - Tomasz Małysa (Buildings, 2023)
Risks are associated with every human activity. Accidental events are recorded in enterprises in the construction industry every day. Those events differ among themselves in the severity of consequences and the number of victims. It is important to reduce them effectively based on the conclusions of accident rate analyses. The study outlines the process of relative risk (RR) analysis and carries out a process of quantitative data prediction to determine priorities for action in the area of accident risk reduction. For the construction industry, being the subject of the analyses, statistical data on the number of persons injured in accidents at work in 2006–2021 were compiled, the relative risk (RR) was determined, and a prediction process using the Brown model and Winters’ model was performed. The relative risk analyses allowed for determining priorities for action in occupational health and safety. Based on the analyses, it was concluded that it is possible to adapt econometric models in the area of relative risk prediction, and the obtained forecast values may be the basis for taking actions regarding occupational health and safety.